Interspecies Comparison of Control Data From Embryo–Fetal Development Studies in Sprague-Dawley Rats, New Zealand White Rabbits, and Göttingen Minipigs. (November 2019) - Paradis, France-Helene; Downey, Anne Marie; Beaudry, Francine; Pinêtre, Clémentine; Ellemann-Laursen, Sisse; Makin, Andy; Hill, Katherine; Singh, Pramila; Hargitai, Judit; Forster, Roy; Tavcar, Robert; Authier, Simon
Species-dependent differences in relative incidence of spontaneous variations and malformations should be considered in the assessment of the translational value of reproductive and developmental safety assessments. The objective of this evaluation was to compare litter parameters and the frequency of external, visceral, and skeletal malformations and variations across species in the Sprague-Dawley rat, New Zealand White rabbit, and Göttingen minipig and to determine whether notable differences exist. Pregnant female rats (n = 824), rabbits (n = 540), and minipigs (n = 70) from vehicle control groups were included in the analysis, equating to 10, 749 rat, 5, 073 rabbit, and 378 pig fetuses collected at term by cesarean delivery. Preimplantation loss was more frequent than postimplantation loss in the rat and rabbit, whereas the opposite was observed in the minipig. Several external and visceral malformations and variations such as domed head, bent tail, abdominal edema, and anal atresia were observed in all 3 species. Visceral malformations of the heart and major blood vessels were remarkably more frequent in the minipig and rabbit, respectively; ventricular and atrium septum defects were observed in 1.9% and 2.1%, respectively, for the minipig fetuses, whereas they were observed in equal or less than 0.02% among the rat and rabbit fetuses evaluated in this study. Understanding species-dependent differences in spontaneous variations and malformations can be useful for the interpretation of embryo–fetal development study results. The current analysis identified relevant differences between commonly used species in reproductive toxicology with potential implications for data assessment.